Relasi Emosi dan Kandōshi Kandō dalam Tindak Tutur Ekspresif Marah pada Drama Jepang Kontemporer The Queen of Villains - Sumpena, Salsadila Hairulnisa; Sunarni, Nani; Ginanjar, Pika Yestia (Jurnal Bahasa dan Sastra, 2025)
This study aims to analyze the use of kandōshi kandō as a marker of the expressive speech act of anger in the Japanese drama The Queen of Villains by examining its forms, delineating its pragmatic functions, and investigating the patterns of inter-utterance relations that construct the emergence of anger expressions within the characters’ dialogues. The research employs a qualitative descriptive method using referential and pragmatic analytical approaches. The data were extracted from dialogue containing angry expressions and subsequently classified according to the forms of kandōshi kandō, their contexts of occurrence, and their pragmatic functions. The findings reveal six major forms haa, nanda, aa, ee, ou, and fuu each signaling a distinct nuance of anger, ranging from cynical rejection and angry surprise to belittlement, emotionally charged criticism, harsh prohibition, and contempt. The analysis further shows that all kandōshi kandō appear within dependent utterance chains (coupling), functioning as direct responses to triggering lines. In addition, their use is pragmatically egalitarian, the drama does not depict power dynamics through linguistic hierarchy, as both senior and junior characters express anger directly without mitigation, producing a pattern of conflictual equality rather than social dominance. These findings contribute to Japanese pragmatic studies by offering a detailed mapping of kandōshi kandō functions specifically within angry expressive acts an area that remains underexplored in prior research, which has tended to focus on anime, radio dramas, or classical performances.